Avaliação do tratamento periodontal associado à terapia fotodinâmica na modulação da inflamação pulmonar em modelo experimental de asma aguda - Candeo, Larissa Carbonera (2016)
Asthma and periodontal disease (PD) present high prevalence and a high economic and social cost. Evidence suggests PD can exert systemic immunomodulatory effects. As the standard periodontal (PT) treatment for PD may not completely eliminate periodontal pathogens, photodynamic therapy (PDT), have been used with promising results. Therefore, the objective of this study was to evaluate whether PT associated with PDT is able to modulate pulmonary inflammation in an experimental model of acute asthma. Seventy- two male Balb/c mice (~ 2 months) were divided into 8 groups (n = 9): (1) basal- sham; (2) with PD; (3) with PD+PT; (4) with PD+PT+PDT, (5) Asthma, (6) A+PD (7) A+PD+PT (8) A+PD+PT+PDT. PD was induced by ligature technique (15 days) and asthma by administration of ovalbumin (OVA) and aluminum hydroxide subcutaneously (days 0 and 7) and nebulization with OVA (3x / week, for 2 weeks). PT was performed with mini-five curettes and PDT with methylene blue (0.005%) with λ = 660 nm, energy density 6.369 J/cm², 9J per point at 2 points. After 21 days, the animals were euthanized for morphological analysis of the lung and the mandible. The cytokines IL-4, IL-5, IL-10, IFN-γ TNF-α, IL-1β and IL-6 and mucus production were evaluated. Total and differential cell counts were performed on LBA and serum. The frequency of inflammatory cells was evaluated by flow cytometry. PD increased the amount of alkaline phosphatase and bone resorption (p<0.05). Asthma group and PD group induced an increase in the total amount of cells (p <0.05) in BAL. However, in the Asthma+PD group there was a decrease in these cells, except for the Asthma+PD+PT+PDT group (p<0.05). The Asthma group induced increase of Th2 profile cytokines and the DP group presented a Th1/Th2 mixed cytokine profile. There was a increased mucus production for Asthma, PD and Asthma+PD+PT+PDT. It is concluded that PD can cause pulmonary inflammation per se. The association of Asthma with PD improves the parameters of pulmonary inflammation. After treatment with PDT, pulmonary inflammation in the asthmatic mice returned near to the baseline asmatic values.